HITS-CLIP analysis of human ALKBH8 reveals interactions with fully processed substrate tRNAs and with specific noncoding RNAs - Cavallin, Ivana; Bartosovic, Marek; Skalicky, Tomas; Rengaraj, Praveenkumar; Demko, Martin; Schmidt-Dengler, Martina Christina; Drino, Aleksej; Helm, Mark; Vanacova, Stepanka (RNA (New York, N.Y.), 2022)
Transfer RNAs acquire a large plethora of chemical modifications. Among those, modifications of the anticodon loop play important roles in translational fidelity and tRNA stability. Four human wobble U-containing tRNAs obtain 5-methoxycarbonylmethyluridine (mcm5U34) or 5-methoxycarbonylmethyl-2-thiouridine (mcm5s2U34), which play a role in decoding. This mark involves a cascade of enzymatic activities. The last step is mediated by alkylation repair homolog 8 (ALKBH8). In this study, we performed a transcriptome-wide analysis of the repertoire of ALKBH8 RNA targets. Using a combination of HITS-CLIP and RIP-seq analyses, we uncover ALKBH8-bound RNAs. We show that ALKBH8 targets fully processed and CCA modified tRNAs. Our analyses uncovered the previously known set of wobble U-containing tRNAs. In addition, both our approaches revealed ALKBH8 binding to several other types of noncoding RNAs, in particular C/D box snoRNAs.
Keywords: RNA transferová; wobble uridine modification; RNA, Untranslated; mcm5U; AlkB homolog 8, tRNA methyltransferasa; ChiP sekvenování; Humans; RNA, Transfer; mcm5s2U; AlkB Homolog 8, tRNA Methyltransferase; HITS-CLIP; lidé; Chromatin Immunoprecipitation Sequencing; ALKBH8; nekódující RNA; Trm9; Anticodon; antikodon